A Therapeutic Antiviral Antibody Inhibits the Anterograde Directed Neuron-to-Cell Spread of Herpes Simplex Virus and Protects against Ocular Disease - Bauer, Dirk; Alt, Mira; Dirks, Miriam; Buch, Anna; Heilingloh, Christiane S.; Dittmer, Ulf; Giebel, Bernd; Görgens, André; Palapys, Vivien; Kasper, Maren; Eis-Hübinger, Anna M.; Sodeik, Beate; et al. (Frontiers in Microbiology, 2017)
Herpes simplex virus (HSV) is a leading cause of blindness and viral encephalitis in the developed world. Upon reactivation from sensory neurons, HSV returns via axonal transport to peripheral tissues where it causes e.g. severe, potentially blinding ocular diseases. In the present study we investigated whether the HSV-1/2 glycoprotein B specific antibody mAb 2c or its humanized counterpart mAb hu2c can protect from ocular disease in a mouse model of HSV-1 induced acute retinal necrosis (ARN). In this model the viral spread from the initially infected to the contralateral eye resembles the routes taken in humans upon HSV reactivation. Systemic antibody treatment prior or early after infection effectively protected the mice from the development of ARN. These observations suggest that the antibody potently neutralized the infection and inhibited the viral transmission, since there was almost no virus detectable in the contralateral eyes and trigeminal ganglia of antibody treated mice. Besides of neutralizing free virus or limiting the infection via activating the complement or cellular effector functions, blocking of the anterograde directed neuron-to-cell spread of HSV represents a viable mode of action how mAb 2c protected the mice from ARN. We proved this hypothesis using a microfluidic chamber system. Neurons and epithelial cells were cultured in two separate compartments where the neurons sent axons via connecting microgrooves to the epithelial cells. Neurons were infected with a reporter HSV-1 strain expressing mCherry, and the co-culture was treated with neutralizing antibodies. In contrast to commercial polyclonal human HSV-neutralizing immunoglobulins, mAb 2c effectively blocked the anterograde directed neuron-to-cell transmission of the virus. Our data suggest that the humanized HSV-1/2-gB antibody protects mice from ocular disease by blocking the neuronal spread of HSV. Therefore, mAb hu2c may become a potent novel therapeutic option for severe ocular HSV infections.